Understanding Society and Culture: a sociology and anthropological approach - Riodique, Francisco C. III (Manila : Mindshapers Co., Inc., 2016)
"This book is designed for college students who are taking a course in sociology and anthropology. This work also includes thorough discussions on the theory of evolution. As a transition from anthropology to sociology, the author of this book included discussion regarding the rise of societies through the agricultural revolution. The author highly suggests that the readers of the book should keep an open mind on the study of humans, society and culture."
Includes references.
English text.
Keywords: Sociology